Polychlorinated dibenzo-p-dioxins and dibenzofurans in a three-stage municipal solid waste gasifier. (1st May 2019) - Hu, Binhang; Huang, Qunxing; Chi, Yong; Yan, Jianhua
Abstract: The quantified emissions of polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofuran (PCDD/Fs) have not yet been reported comprehensively with the whole gasifier system. In this study, the emission characteristics of PCDD/Fs concentration, toxicity equivalent quantity, reaction mechanism are examined for a three-stage gasification system. This system first features the pyrolysis of municipal solid waste (MSW), next the oxidation of the pyrolysis products and as a final third step its high temperature cracking on two types of char (coal coke and rice husk char). The effect of the reduction temperature (800, 900, and 1000 °C) and char type have been experimentally evaluated. In general, the final I-TEQ of PCDD/Fs are controlled at a low level (0.068–0.085 ng I-TEQ/Nm 3 ), due to the absence of oxygen and decomposition of PCDD/Fs during reduction at a high temperature. Meanwhile, the PCDD/Fs concentration (P = 4 to 8) decreased significantly, maintaining in a range of 1.32–1.58 ng/Nm 3 . The decrease of 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD), 1, 2, 3, 7, 8-pentachlorodibenzo-p-dioxin (PeCDD) and 2, 3, 4, 7, 8-pentachlorodibenzo-furan (PeCDF) collectively resulted in the decline of total I-TEQ values for coal char after reduction reaction, while the 2, 3, 7, 8-TCDD and 1, 2, 3, 7, 8-PeCDD both increased their contribution in total I-TEQ values. The low-chlorinated PCDDs were easier to transform into high-chlorinated PCDDs for coal char during the reduction stage, which is opposite to that for rice husk char. The chlorophenol precursor routes apparently played an increasing role in PCDD/Fs formation with the reduction temperature increasing from 800 to 1000 °C. Furthermore, the primary PCDD/Fs formation reactions have converted from the chlorophenol precursor routes (secondary reactions) into de novo reactions for the coal char sample, while the chlorophenol precursor reactions strengthened their leading role during the reduction stage for rice husk char. Graphical abstract: Image 1 Highlights: The emission characteristics of PCDD/Fs are studied on a three-stage co-gasification system. The I-TEQ of PCDD/Fs in syngas can be controlled as low as 0.068 ng/Nm 3 after the reduction reaction. The low-chlorinated PCDDs were easier to transform into high-chlorinated PCDDs for coal char. The chlorophenol precursor routes played an increasing role in PCDD/Fs formation with increasing temperature.